Influence of gate-source/drain misalignment on the performance of bulk FinFETs by a 3D full band Monte Carlo simulation - 王骏成 杜刚 魏康亮 曾琅 张兴 刘晓彦 (Journal of semiconductors, 2013)
We investigate the influence of gate-source/drain （G-S/D） misalignment on the performance of bulk fin field effect transistors （FinFETs） through the three-dimensional （3D） full band Monte Carlo simulator. Several scat- tering mechanisms, such as acoustic and optical phonon scattering, ionized impurity scattering, impact ionization scattering and surface roughness scattering are considered in our simulator. The influence of G-S/D overlap and underlap on the on-states performance and carrier transport of bulk FinFETs are mainly discussed in our work. Our results show that the on-states currents increase with the increment of G-D/S overlap length and the positions of a potential barrier and average electron energy maximum vary with the G-D/S overlap length. The carrier transport phenomena in bulk FinFETs are due to the effect of scattering and the electric field in the overlap/underlap regime.